Implementasi Penerapan Resiko Keamanan Industri 4.0 Berbasis Nilai Nilai Kebangsaan UUD 1945 dalam Proses Produksi PT.Toyota Astra Indonesia - Muhammad Rifda H; Edy Soesanto; Titan Shafrial Chaesar H; Teta Wahyu Sibero T (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
Industrial safety is an important aspect in maintaining a safe work environment and in accordance with applicable legal regulations. In the context of manufacturing companies such as PT. Toyota Astra Indonesia, implementing industrial safety is crucial to ensure the production process runs smoothly and safely for its workers. This article discusses the implementation of industrial security based on the 1945 Constitution (UUD 1945) in the production process of PT. Toyota Astra Indonesia. Industrial security implementation steps carried out by PT. Toyota Astra Indonesia includes the implementation of strict work safety standards, supervision of the use of work equipment, employee training on safety, and regular audits to ensure compliance with regulations contained in UUD No. 1 of 1970 concerning Work Safety. Apart from that, the company also pays attention to environmental protection aspects in its production process in supervision so as to integrate work safety with environmental sustainability. In the context of the 1945 Constitution, the implementation of industrial security at PT. Toyota Astra Indonesia includes a company's code of ethics in (UUD No. 40 of 2007 Article 74), policies and compliance with the law, health and safety policies at work, and Corporate Social Responsibility (CSR) policies directed at ensuring that workers' rights are respected. guaranteed in the 1945 Constitution to be fulfilled properly. In this way, the company ensures that a safe and conducive work environment is the right of every worker in accordance with applicable legal provisions. By implementing industrial security based on the 1945 Constitution, PT. Toyota Astra Indonesia not only ensures compliance with legal regulations, but also supports the country by contributing to providing automotive capabilities and maintaining the company's reputation and increasing overall productivity. In addition, the integration of job security and environmental protection also reflects the company's commitment to sustainability and corporate social responsibility.